A new interpretation of Qohelet 10:10 - Pinker, Aron (Old Testament essays, 2011)
We offer a new interpretation of Qoh 10:10, which is based on the view that the unit consisting of vv. 10-11 is an expansion of the original proverb אִם־קֵתָת תַבַּרְזֶל אֵיו יִתְרוֹן לְבַﬠַל תַלָּשוֺן, "If a blade became blunt, then the owner of the blade (תַלָּשוֹן) has no advantage." The rest of the unit is an elaboration of the idea that a blunted tool offers no advantage to its owner. We suggest that Qoh 10:10 consists of a rhetorical question (10:10a), and an answer which advises proper training for a battle-axe user (10:10b). Qohelet exploits the example of a battle-axe user to bring home the idea that honing wisdom skills would keep them useful. The hallmark of Wisdom is sharpness of thought encapsulated in few words, as is the ease of using effectively a sharp axe. This advantage is lost when the tool becomes blunted, and can be maintained by training and exercise.